COMMUNITY SERVICE EDUCATION ON GROWTH AND DEVELOPMENT AND SURVIVAL OF HIGH-RISK INFANTS THROUGH MIDWIFE ASSISTANCE AT THE DELIMA CLINIC - Rohmatun Nazilah; Barirah; Santalia Laoli (Jurnal Masyarakat Indonesia (Jumas), 2024)
High-risk infants require intensive monitoring and appropriate stimulation to ensure optimal growth and development and increase their chances of survival. Parents' lack of understanding of danger signs and special needs in high-risk infants is often an obstacle in efforts to prevent developmental disorders. This community service activity aims to provide education and assistance by midwives related to optimizing the growth and development of high-risk babies at the Delima Clinic. The program will be carried out on April 24, 2024 through counseling methods, demonstrations of growth and development stimulation, and direct assistance. The results of the evaluation showed an increase in maternal knowledge in recognizing the baby's developmental stage and independence in providing appropriate stimulation according to the needs of high-risk babies. This continuous education and mentoring has proven to be effective in strengthening the role of parents in supporting the quality of life and development of babies comprehensively